Profile of High School Students' Understanding of Atomic Structure - Yaqiin, Ainul; Habiddin, Habiddin; Rahmawati, Benita; Secharlati, Chika Kirana N (Universitas Negeri Padang, 2024)
Understanding fundamental chemistry concepts is necessary to study the following concepts at a higher level. Atomic structure is a prerequisite topic that must be mastered to study advanced concepts. If students have difficulty understanding the concept, it can affect their understanding of other chemistry concepts. This study aims to describe and identify differences in understanding the atomic structure of 75 students in grades 10, 11, and 12. The validated instrument in the form of structured short answer questions was applied. The data was analyzed descriptively using parametric statistics, namely the Anova One Way and Post Hoc Tukey tests. The results of the analysis stated that the understanding of atomic structure material for students in grades 12 11 10. The comprehension of grade 10 and 11 students is included in the high category, and for grade 12, it is very high. There was a significant difference in the understanding of atomic structure material between students in grades 10, 11, and 12, and there was a positive relationship between students' understanding of atomic structure material and grade level.